Population Growth and Competition of Tribolium castaneum and S. oryzae in Wheat Flour - Irwan Hanafi (Pendidikan Biologi FKIP UMMY, 2023)
There are insects in their life that are pests. Most of the insect pests attack agricultural products stored in warehouses (Warehouse insects). There are more than 100 species of warehouse insects and 20 of them are cosmopolitan (Winarno, 1982). Among the barn insect species, Tribolium castaneum and S.oryzae are the most commonly found in rice, peanuts, cocoa beans, nutmeg, wheat flour, tapioca flour, copra and as a type of cake. Based on this, a study was carried out with the title